2022
DOI: 10.1002/agm2.12222
|View full text |Cite
|
Sign up to set email alerts
|

Chinese expert consensus on assessment of cognitive impairment in the elderly

Abstract: Cognitive impairment is a term that refers to the impairment of one or more cognitive domains to varying degrees caused by a variety of reasons. It is under a high prevalence, many risk factors, complex etiology, and great harm to the elderly population. Early screening, diagnosis, and intervention for cognitive impairment in the elderly are of great importance. However, at present, the recognition rate of cognitive impairment for the elderly in China is low, the rate of missed diagnosis is high, and the evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…We relied on expert consensus and clinical guidelines that considered the safe and feasible approach when acupuncture therapy started within 72 hours after injury. [30,31] In this study, the acupuncture points were selected based on traditional Chinese medicine theory, our previous pilot study, and summaries of the medical experts' experiences. For example, the acupuncture points of GV26, PC6, and SP6 were selected on the basis of Shi's Xingnaokaiqiao theory, which has achieved significant effects in the treatment of acute and critical cerebrovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…We relied on expert consensus and clinical guidelines that considered the safe and feasible approach when acupuncture therapy started within 72 hours after injury. [30,31] In this study, the acupuncture points were selected based on traditional Chinese medicine theory, our previous pilot study, and summaries of the medical experts' experiences. For example, the acupuncture points of GV26, PC6, and SP6 were selected on the basis of Shi's Xingnaokaiqiao theory, which has achieved significant effects in the treatment of acute and critical cerebrovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension has been identified as a risk factor associated with cognitive impairment. 1,2 Previous studies have demonstrated an inverse correlation between blood pressure and the prevalence of cognitive impairment. 3 Furthermore, strict blood pressure management programs have been proposed to mitigate cardiovascular and cerebrovascular events in the oldest old population.…”
Section: Introductionmentioning
confidence: 99%
“…This includes cognitive decline, which, in severe cases, can develop into cognitive impairment, and subsequently dementia. Cognitive impairment generally refers to varying degrees of cognitive function decline caused by several factors (including memory, computation, temporal and spatial orientation, structural ability, executive ability, language understanding, expression and application, etc.,) ( Ni et al, 2022 ). It is now established that cognitive impairment is associated with various adverse outcomes such as falls, prolonged hospitalization and readmission ( Buslovich and Kennedy, 2012 ; Callahan et al, 2015 ; Ma et al, 2021b ).…”
Section: Introductionmentioning
confidence: 99%